STUDI PENENTUAN TINGKAT KEKUMUHAN DAN SKALA PRIORITAS PENANGANAN PERMUKIMAN KUMUH DI KABUPATEN BOLAANG MONGONDOW SELATAN - Tangkudung, Theogive Hosea; Tilaar, Sonny; Sela, Rieneke L.E. (SPASIAL, 2021)
South Bolaang Mongondow is one of the regencies located in North Selawesi Province which is one of the regencies that is growing rapidly. Along with the increase in population, inadequate infrastructure, facilities and public utilities have resulted in many people in this district living in places that do not meet the standards, which are slums. Slum areas in South Bolaang Mongondow Regency according to the 2016 South Bolaang Mongondow Regency slum decree, there are 23 villages that are included in slum areas, these slums have three classifications, namely, heavy slums, medium slums and light slums. Based on this classification, it is combined with land status and other considerations so that a priority scale for handling slum settlements can be drawn up and how the pattern of handling slum settlements in Bolaang Mongondow Selatan Regency can be. The method used is a multi-criteria analysis method with 9 indicators, namely building conditions, environmental road conditions, environmental drainage conditions, drinking water supply conditions, wastewater management conditions, waste management conditions, fire protection conditions and land status and other considerations. Based on the results of the study, it was found that 16 villages would be treated with a rejuvenation pattern, 1 village would be resettled and 6 villages would be treated with a restoration pattern.KeywordÂ  : Slums, Slum Level, Priority Scale, slum settlement pattern